Gene-Centric Laws in the Postgenomic Era: The Need for Protection of Epigenetic Information - Davidson, Emily (Science and Technology Law Review, 2024)
In recent decades, special attention has been given to the privacy and discrimination risks associated with genetic information. Federal, state, and international laws all contain specific protections for the use of genetic information in a variety of contexts, including insurance and employment. Yet the very considerations motivating special protections for genetic information extend beyond mere genetics. Epigenetics involves the study of heritable changes in gene function that do not involve changes in the DNA sequence. Epigenetic data shares a number of normative similarities and policy concerns with genetic data, and in some ways, presents an even greater privacy and nondiscrimination risk than genetic data. However, epigenetic information remains unprotected by existing genetic privacy and nondiscrimination laws, which are based on an outdated conception of health and disease, focused narrowly on genes and genetic information. This Note argues that epigenetic information warrants the same protections as genetic information and calls for an amendment of existing genetic privacy and nondiscrimination laws to broaden the definitions of the data at stake to encompass epigenetic and other postgenomic information.